Significance of lactate dehydrogenase in prediction of pregnancy induced hypertension and its complications - Kaur, Rupinder; Sonowal, Ramesh (International Journal of Medical Research and Review, 2016)
Objectives: To compare serum Lactate Dehydrogenase (LDH) level of normotensive pregnant women with those of preeclamptic and eclamptic women. To determine the relationship of levels of serum Lactate dehydrogenase with severity of pregnancy induced hypertension and its complications. Method: The study was carried out on pregnant hypertensive patients attending outpatient department of Obstetrics and Gynaecology department, AMCH Dibrugarh, Assam from 1st July 2013 to 30th June 2014. Normotensive pregnant women were taken as controls. Each serum sample from the control group as well as study group was estimated for Lactate Dehydrogenase using standard methods and a comparison was drawn and analyzed using t-test and chi-square test. Results: Serum Lactate Dehydrogenase level was high in the study group. The level of this enzyme was normal in the control group. Conclusion: Serum Lactate Dehydrogenase levels in patients suffering from preeclampsia and its complications are consistently higher as compared to the normotensive pregnant patients. The usefulness of this enzyme as marker of the severity of pregnancy induced hypertension and its universal inclusion along with other cardiac enzymes in the panel of investigations of pregnant women needs further large scale comparative studies.